Avaliação da carga parasitária de helmintos e protozoários em bezerros manejados em sistema orgânico - da Silva, Jenevaldo Barbosa [UNESP]; Guimaraes Soares, Joao Paulo; da Fonseca, Adivaldo Henrique (Universidade Estadual de Londrina (UEL), 2012)
The objective of this study was to evaluate the influence of helminths eggs and protozoan oocysts elimination in calves' feces kept in organic system production. The study was conducted from January 2008 to December 2009. Coproparasitological examinations were carried biweekly of 18 calves in pastures rotating system on Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) Agrobiology. The egg counting average data had been submitted to the Kruskal Willis test and the larvae counting percentile values to the qui-square test. The average counting of eggs per gram of faces (EGF) varied of 250 the 800, characterizing low and moderate infection. Animals with inferior age the six months had presented superior results of EGF (P <.05) to the ones of between six and twelve months age. The biggest degrees of infection had been observed in the late spring and summer. In the fecal examinations was identified the following helminths: Haemonchus (73%), Trichostrongylus (24%) and Oesophagostomum (3%). The practical handling adopted in organic system production had been capable to keep the animals in moderate levels of infection, being indicated that it had helmintoses control in rotating system of pastures.
Strategic management of pastures to control helminths and coccidia of calves in organic system
Keywords: Dairy cattle; Haemonchus; rotational grazing